2016 Australian Communications Theory Workshop (AusCTW) 2016
DOI: 10.1109/ausctw.2016.7433656
|View full text |Cite
|
Sign up to set email alerts
|

A game-theoretic perspective on communication for omniscience

Abstract: We propose a coalition game model for the problem of communication for omniscience (CO). In this game model, the core contains all achievable rate vectors for CO with sumrate being equal to a given value. Any rate vector in the core distributes the sum-rate among users in a way that makes all users willing to cooperate in CO. We give the necessary and sufficient condition for the core to be nonempty. Based on this condition, we derive the expression of the minimum sum-rate for CO and show that this expression … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0

Year Published

2016
2016
2018
2018

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 6 publications
(17 citation statements)
references
References 23 publications
0
17
0
Order By: Relevance
“…A different coalition-game model for the CDE problem was recently proposed in [12]. This model, however, differs from our work in two aspects: (i) the utility function under the consideration is different from ours, and (ii) the criteria for the stability of the grand coalition is different from the Pareto optimality being considered here.…”
Section: A Related Workmentioning
confidence: 82%
“…A different coalition-game model for the CDE problem was recently proposed in [12]. This model, however, differs from our work in two aspects: (i) the utility function under the consideration is different from ours, and (ii) the criteria for the stability of the grand coalition is different from the Pareto optimality being considered here.…”
Section: A Related Workmentioning
confidence: 82%
“…3) The egalitarian solution [19] aims to equalize the rate/cost allocation in the optimal rate region regardless of the marginal 3 The fundamental partition P * is an optimizer that determines the minimum sum-rate R * [9]. See also Section II-A.…”
Section: A Summary Of Main Resultsmentioning
confidence: 99%
“…They are also very grateful to Prof. Chung Chan, Mr. Qiaoqiao Zhou and Prof. Tie Liu for their early contributions to the coalitional game model of CO and the decomposition property of the egalitarian solution in [1], [3], as well as the insightful discussions about the interpretation of the Shapley value. The authors would like to thank Dr. Ali Al-Bashabsheh for his comments on the egalitarian solution in Section V of this paper.…”
Section: Acknowledgmentmentioning
confidence: 99%
“…Steps 7 and 8 in the SPLIT algorithm indicate an adaptive rate update method: In step 7, since r * C\X ≥ f (X) w(X) w C\X , 10 we first assign f (X) w(X) w C\X to r * C\X and determine the remaining rates by calling SPLIT(C \X, g, w C\X ) in step 8. It is easy to see that r * V ∈ P (H, ≤) after each execution of step 7.…”
Section: Adaptive and Distributed Implementationmentioning
confidence: 99%
“…For a system where the terminals (also known as users or nodes) are equally privileged, e.g., a WSN, we always seek to attain fairness in the SW region. Several game-theoretic contributions in [8][9][10] showed that the Shapley value [11] is one solution within the SW region. However, computing the Shapley value is intractable in large scale systems due to the exponentially growing complexity in the number of terminals.…”
Section: Introductionmentioning
confidence: 99%